Changes of adjacent segment biomechanics after anterior cervical interbody fusion with different profile design plate: single- versus double-level. Issue 6 (26th April 2023) - Jin, Lin-Yu; Wei, Ke; Feng, Da-Ming; Li, Jian-Dong; Song, Xiao-Xing; Yin, Hong-Ling; Li, Xin-Feng
Abstract: Low-profile angle-stable spacer Zero-P is claimed to reduce the morbidity associated with traditional plate and cage construct (PCC). Both Zero-P and PCC could achieve comparable mid- and long-term clinical and radiological outcomes in anterior cervical discectomy and fusion (ACDF). It is not clear whether Zero-P can reduce the incidence of adjacent segment degeneration (ASD), especially in multi-segmental fusion. This study aimed to test the effect of fusion level with Zero-P versus with PCC on adjacent-segment biomechanics in ACDF. A three-dimensional finite element (FE) model of an intact C2–T1 segment was built and validated. Six single- or double-level instrumented conditions were modeled from this intact FE model using Zero-P or the standard PCC. The biomechanical responses of adjacent segments at the cephalad and caudal levels of the operation level were assessed in terms of range of motion (ROM), stresses in the endplate and disc, loads in the facets. When comparing the increase of adjacent-segment motion in single-level PCC fusion versus Zero-P fusion, a significantly larger increase was found in double-level fusion condition. The fold changes of PCC versus Zero-P of intradiscal and endplate stress, and facet load at adjacent levels in the double-level fusion spine were significantly larger than that in the single-level fusion spine during the sagittal, the transverse, and the frontal plane motion. The increased value of biomechanical features was greater at above segment than that at below. The fold changes of PCC versus Zero-P at adjacent segment were most notable in flexion and extension movement. Low-profile device could decrease adjacent segment biomechanical burden compared to traditional PCC in ACDF, especially in double-level surgery. Zero-P could be a good alternative for traditional PCC in ACDF. Further clinical/in vivo studies will be necessary to explore the approaches selected for this study is warranted.